MEDIA PEMBELAJARAN BAHASA IMAI (INDONESIA, MANDARIN, ARAB DAN INGGRIS) BERBASIS MULTIMEDIA - Samsudin Samsudin; Aninda Muliani Harahap; Muhammad Rafli Hakim (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
Science and technology is experiencing rapid development and progress in the world of education. One of them is technology in learning media. Language recognition in children needs to be improved on the media. The purpose of this research is to build interactive learning media for the introduction of IMAI languages (Indonesian, Mandarin, Arabic, and English) to broaden students' knowledge of languages. With the existence of learning media packaged with animation using Adobe Flash, it can also attract students' interest in learning languages. This learning media uses the MDLC (Multimedia Development Life Cycle) development model with 6 stages. The result of this research is an interactive learning media for the introduction of the IMAI language (Indonesian, Mandarin, Arabic, and English) at the elementary level with material aimed at grade 3 elementary school students